1995
DOI: 10.1002/ijc.2910620306
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth‐factor‐binding protein 3 is decreased in early‐stage operable pre‐menopausal breast cancer

Abstract: Insulin-like growth factor I (IGF-I) is a potent mitogen for human breast-cancer cells in vitro. In circulation, most of IGF-I is bound to IGF-binding protein 3 (IGFBP-3). This high-affinity binding is thought to have an important limiting effect on the availability of IGF-I for biological activity. To assess the availability of IGF-I for receptor binding, we determined serum levels of IGF-I and IGFBP-3 and IGF-I/IGFBP-3 ratios. In a case-control study, 150 women aged 38 to 75 years presenting with stage-I or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
107
1
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(121 citation statements)
references
References 30 publications
10
107
1
3
Order By: Relevance
“…5 Previous studies have suggested that using measures such as IGF-I/IGFBP-3 ratio or IGFBP-3 adjusted OR might be more accurate than IGF-I alone in quantifying the association between IGF-I levels and premenopausal breast cancer. 7,30 Although we cannot conclude whether these alternative measures are better than absolute IGF-I level or not, we found that absolute circulating IGF-I was one of the good measures to evaluate the association between IGF-I levels and premenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 81%
“…5 Previous studies have suggested that using measures such as IGF-I/IGFBP-3 ratio or IGFBP-3 adjusted OR might be more accurate than IGF-I alone in quantifying the association between IGF-I levels and premenopausal breast cancer. 7,30 Although we cannot conclude whether these alternative measures are better than absolute IGF-I level or not, we found that absolute circulating IGF-I was one of the good measures to evaluate the association between IGF-I levels and premenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 81%
“…Higher levels of IGF-1 were associated with breast cancer both in pre-and post-menopausal women in one study (Peyrat et al, 1993) and only in premenopausal women in two other studies (Bruning et al, 1995;Bohlke et al, 1998) where lower levels of IGFBP-3 were also found in premenopausal cases compared to controls. No associations were observed for these variables and breast cancer in postmenopausal women in two other investigations (Bruning et al, 1995;Hankinson et al, 1997) and in one study on premenopausal women (Del Giudice et al, 1998), although in the latter the control group chosen, potentially at high risk. In a small case -control study IGF-1 and IGFBP-3 were found, respectively, directly and indirectly associated with premenopausal ductal carcinoma in situ (Bohlke et al, 1998).…”
Section: Glycemic Index In Chronic Disease Ls Augustin Et Almentioning
confidence: 90%
“…Published studies variously report moderate elevation in premenopausal cases (Bruning et al, 1995), marked elevation in both pre-and post-menopausal cases (Peyrat et al, 1993) and no association (Favoni et al, 1995). IGF1 is synthesized mainly in the liver under growth hormone stimulation but it is not stored locally.…”
Section: Igf1 Hyperinsulinaemia and Breast Cancermentioning
confidence: 99%